VPS54 and the wobbler mouse - Schmitt-John, Thomas (Frontiers in Neuroscience, 2015)
The wobbler mouse is an animal model for human motor neuron disease, such as amyotrophic lateral sclerosis (ALS). The spontaneous, recessive wobbler mutation causes degeneration of upper and lower motor neurons leading to progressive muscle weakness with striking similarities to the ALS pathology. The wobbler mutation is a point mutation affecting Vps54, a component of the Golgi-associated retrograde protein (GARP) complex. The GARP complex is a ubiquitously expressed Golgi-localized vesicle tethering complex, tethering endosome-derived vesicles to the trans Golgi network. The wobbler point mutation leads to a destabilization of the Vps54 protein and thereby the whole GARP complex. This effectuates impairments of the retrograde vesicle transport, mis-sorting of Golgi- and endosome localized proteins and on the long run defects in Golgi morphology and function. It is currently largely unknown how the destabilization of the GARP complex interferes with the pathological hallmarks, reported for the wobbler motor neuron degeneration, like neurofilament aggregation, axonal transport defects, hyperexcitability, mitochondrial dysfunction and how these finally lead to motor neuron death. However, the impairments of the retrograde vesicle transport and the Golgi-function appear to be critical phenomena in the molecular pathology of the wobbler motor neuron disease.